Die Ordnung des Wissens: Was leistet Michel Foucaults Diskursanalyse für eine kritische Gesellschaftstheorie? - Kappeler, Florian (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2008)
In its first part, the article deals with Michel Foucaults "discourse analysis", as developed in his "Archaeology of knowledge". The second part considers the concept of discourse in relation to Foucaults "analytic of power" and to a critical theory of society inspired by Karl Marx, especially Louis Althussers notion of ideology. Thus, on the one hand, some propositions for a methodology of discourse analysis are being made, and, on the other hand, its position within a project of critical social theory is discussed.